2018
DOI: 10.1038/s41467-017-02670-2
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular recombination in methylammonium lead triiodide perovskite is an inverse absorption process

Abstract: Photovoltaic devices based on metal halide perovskites are rapidly improving in efficiency. Once the Shockley–Queisser limit is reached, charge-carrier extraction will be limited only by radiative bimolecular recombination of electrons with holes. Yet, this fundamental process, and its link with material stoichiometry, is still poorly understood. Here we show that bimolecular charge-carrier recombination in methylammonium lead triiodide perovskite can be fully explained as the inverse process of absorption. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
276
7
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 280 publications
(334 citation statements)
references
References 68 publications
(82 reference statements)
34
276
7
4
Order By: Relevance
“…, where m * e , m * h and µ * are the electron, hole and reduced effective masses respectively. The exciton binding energy is calculated using the expression E b = µ * / 2 ∞ × ERy eV, with ERy = 13.60565 eV, the reduced effective mass µ * = 0.11 me and the high-frequency dielectric constant ∞ = 5.8. a b c (Davies et al, 2017) d e (Pérez-Osorio et al, 2015) f (Hirasawa et al, 1994) g (Poglitsch and Weber, 1987) h (Miyata et al, 2015) conduction band edges exhibit a parabolic profile over a range of 300 meV (FIG. 4b).…”
Section: Fig 3bmentioning
confidence: 99%
See 4 more Smart Citations
“…, where m * e , m * h and µ * are the electron, hole and reduced effective masses respectively. The exciton binding energy is calculated using the expression E b = µ * / 2 ∞ × ERy eV, with ERy = 13.60565 eV, the reduced effective mass µ * = 0.11 me and the high-frequency dielectric constant ∞ = 5.8. a b c (Davies et al, 2017) d e (Pérez-Osorio et al, 2015) f (Hirasawa et al, 1994) g (Poglitsch and Weber, 1987) h (Miyata et al, 2015) conduction band edges exhibit a parabolic profile over a range of 300 meV (FIG. 4b).…”
Section: Fig 3bmentioning
confidence: 99%
“…The parabolicity of the conduction and valence band edges has important implications in the understanding of both absorption and recombination mechanisms in CH 3 NH 3 PbI 3 . Using a combined experimental and theoretical analysis of the optical absorption lineshape, (Davies et al, 2017) showed that the optical absorption spectrum of CH 3 NH 3 PbI 3 can be modelled using the Elliot's theory (Elliott, 1957) up to 100 meV above the absorption onset. Within this premise, (Davies et al, 2017) decoupled the excitonic and continuum part of the absorption spectrum, and calculated the bimolecular recombination rate using the van Roosbroek-Shockley formalism (van Roosbroek and Shockley, 1954).…”
Section: Fig 3bmentioning
confidence: 99%
See 3 more Smart Citations